Effect of Water Storage on the Micro-shear Bond Strength of Two Self-etch Adhesives to Enamel and Dentin - Z. Jaberi Ansari; AR. Sadr (Tehran University of Medical Sciences, 2007)
Objective: This study evaluated the influence of storage time on micro-shear bond strength of two self-etching materials to enamel and dentin. Materials and Methods: Human third molar teeth were sectioned to 1.5 mm thick beams and randomly divided into 2 groups. In group I, SE Bond and in group II, Tri-S Bond was used to bond a composite rod (AP-X) to each treated surface. Specimens were prepared according to manufacturer instructions. Each group was further divided into three subgroups according to water storage time; 1 day, 6 and 12 months. Micro-shear bond strengths were determined under a crosshead speed of 1mm/min using a universal testing machine and expressed in MPa. Data was statistically analyzed by ANOVA and Dunnett post hoc test. Results: Micro-shear bond strength of two adhesives to enamel and dentin showed a slight but not significant decrease over time (P>0.5). After one day, the mean bond strength of enamel in groups I and II were 39.47 and 34.65 MPa and in dentin were 45.20 and 36.0 MPa respectively. There was no statistically significant difference between two materials (P=0.190, P=0.082). After six months the bond strength in group I and II was 35.93 and 35.18 MPa for enamel, and 38.27and 35.19 MPa for dentin respectively, these differences was not statistically significant (P=0.520, P=0.179). After one year, the bond strength of enamel in groups I and II, were 34.47and 29.91 MPa, and in dentin were 33.86 and 32.53 MPa respectively which was not statistically significant (P=0.609, P=0.991). Conclusion: The micro-shear bond strength of both adhesives to enamel and dentin decreased slightly over time; however these decreases were not statistically significant.